Innate and Learned Olfactory Responses in a Wild Population of the Egg Parasitoid Trichogramma (Hymenoptera: Trichogrammatidae). Issue 1 (13th December 2016) - Wilson, J. Keaton; Woods, H. Arthur
Abstract: Parasitoid insects face the fundamental problem of finding a suitable host in environments filled with competing stimuli. Many are deft sensors of olfactory cues emitted by other insects and the plants they live on, and use these cues to find hosts. Using olfactory cues from host-plants is effective because plants release volatile organic compounds (VOCs), in response to herbivory or oviposition, that contain information about the presence of hosts. However, plant-produced cues can also be misleading because they are influenced by a variety of stimuli (abiotic variation, infection and multiple sources of induction via herbivory or oviposition). Flexible behavior is one strategy that parasitoids may use to cope with variation in olfactory cues. We examine the innate and learned responses of a natural population of wasp egg parasitoids ( Trichogramma deion and Trichogramma sathon ) using a series of laboratory and field Y-olfactometer experiments. Wasps typically attack eggs of the hawkmoth Manduca sexta and Manduca quinquemaculata on native Datura wrightii plants in the southwestern United States. We show that Trichogramma wasps responded innately to VOCs produced by D. wrightii and could distinguish plants recently attacked by M. sexta from non-attacked plants. Furthermore, adult Trichogramma wasps were able to learn components of the VOC blend given off by D. wrightii, though they did not learn during exposure as pupae. By further exploring the behavioral ecology of a natural population of Trichogramma, we gain greater insight into how egg parasitoids function in tri-trophic systems.